(untitled) (Asian Journal of Pharmaceutics (AJP), 2016)
Context: Nowadays scientist increasing interest in the field of research and development to investigate the employ of Indian traditional medicine in the treatment and prevention of diarrhea. Frequent of passage of three or more loose or watery stools and unformed feces per day indicates diarrhea. Diarrhea is a major cause of ill-health, especially for children because, particularly, rotavirus responsible for it. Traditionally, Tamarindus indica seed is employed in the management of diarrhea. Aims: The aim of recent research to study the traditional claim of ethanolic (alcoholic) extract of T. indica L. (EETI) seed for antidiarrheal activity in albino Wistar. Materials and Methods: The extract of T. indica seeds was developed using successive solvent extraction using ethanol at room temperature in a soxhlet apparatus. The preliminary phytochemical study was carried out for the identification of active phytoconstituents that elicit antidiarrheal action in albino Wistar rats. Statistical Analysis Used: Yes. The results of in-vivo pharmacological studies were represented as mean Â± standard error of mean. The total variations present in data were evaluated using Graph Pad Prism 5 project software analysis of variance followed by Studentâ€™s t-test. The result was considered statistically significant when the value of P < 0.05 versus control. Results: The preliminary phytochemical investigation of EETI seed indicated the presence of alkaloids, flavonoids, carbohydrates, glycosides, and tannins phytoconstituents. Acute toxicity test was investigated and performed the antidiarrheal activity in albino Wistar rats. EETI indicated neither any toxic effect nor mortality in albino Wistar rats up to the 2000 mg/kg, p.o. dose for 48 h and then up to 14 days. EETI seed showed a significantly antidiarrheal activity 78.23% at a dose of 400 mg/kg, p.o. in comparison to control group in the castor oil induced diarrhea in albino Wistar rats. Phytochemical investigation indicated the existence of flavonoids and tannins in the EETI, so the possible mechanism for the reduction of diarrheal episode may be due to the presence of these contents of the extract. Conclusions: It was concluded that the significant antidiarrheal activity have been shown by EETI seeds. EETI played a significant role in the management of diarrhea.